Pneumothorax as a Presentation of Tuberous Sclerosis-Associated Lymphangioleiomyomatosis - Duarte Lages Silva (European Journal of Case Reports in Internal Medicine, 2019)
Tuberous sclerosis complex (TSC) is a rare, autosomal dominant disorder with a recognized phenotypic variability with clinical manifestations developing continuously throughout life. The follow-up of TSC patients is challenging. The authors present a case with a definite diagnosis of TSC with known skin, renal, hepatic and neuropsychiatric involvement, whose diagnosis of TSC-associated lymphangioleiomyomatosis was establish at a late stage after the patient had presented with recurrent pneumothorax. Notwithstanding, mammalian target of rapamycin inhibition therapy was initiated.